That Which Was Ecstasy Shall Become Daily Bread - Barry M. Andrews (Religions, 2017)
This paper attempts to answer three questions: (1) Was Emerson a mystic? (2) If so, what is the nature of his mysticism? (3) How has his understanding of mysticism influenced by Unitarian theology and spiritual practice? In doing so, it draws upon historical and contemporary studies of mysticism and mystical experience, including those of William James, Leigh Eric Schmidt, and Bernard McGinn among others; the writings of Emerson, including his essays, lectures, and journals, and, finally, the testimonies of his contemporaries and succeeding generations of Unitarian religious leaders. Answering the first question in the affirmative, the paper examines Emerson’s understanding of mysticism as a departure from a devotional form of mysticism focused on relationship with a personalized deity and toward a naturalistic, transpersonal type of mysticism, and traces its influence within the context of Unitarian history.